Is there anything Left?: A Global Analysis on Changes in Engagement with Political Content on Twitter in the Musk Era - Brahmani Nutakki; Rosa M. Navarrete; Giuseppe Carteny; Ingmar Weber (Journal of Quantitative Description: Digital Media)
Over the past few years, Twitter (now X) has become an influential platform for political discourse. However, prior research suggests that Twitter may be biased towards right-wing content. Following the change in ownership in October 2022, there have been several changes to Twitter’s policies, particularly in content flagging and Twitter Blue Verification. Understanding how any shifts in outcomes vary across different political ideologies is important for comprehending the evolving political discourse, especially given recent developments. To explore this issue, we examine shifts in engagement (characterized by likes and retweets) for political figures before and after November 2022, focusing on describing how engagement has changed over time. We perform a global analysis by collecting tweets from 6550 accounts belonging to political leaders and parties from twelve countries among the ones with the highest user activity on the platform, namely, Argentina, Brazil, Canada, Colombia, France, Germany, India, Japan, Mexico, Spain, the United Kingdom, and the United States, between June 2021 and June 2023. Our findings indicate that the number of likes on political tweets increased after November 2022. However, we observe that the number of retweets decreased significantly, along with a marginal decrease in the likes-to-retweet ratio, with no statistically significant difference between the Left and the Right. Our study is the first to offer a global perspective by examining how platform engagement has shifted during the Musk Era. To support further research, we release the data on politicians and parties used in this study, with their Twitter data available upon request.